1997
DOI: 10.1111/j.1365-2621.1997.tb04442.x
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin as an Antimicrobial for Producing Shelf‐stable Strawberry Puree

Abstract: The utilization of vanillin was studied as a natural antimicrobial in a combined technology for producing a shelf-stable strawberry purée. Mild heat treatment (blanching) was combined with addition of 3,000 ppm vanillin and 500 ppm ascorbic acid and adjustment of water activity (a w ) to 0.95 and pH to 3.0. This prevented growth of both native and inoculated flora for ≥60 days storage at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 14 publications
1
56
0
3
Order By: Relevance
“…Natural vanilla extract from reported that vanillin is able to suppress the proliferation of cancer cells and prevent chemically and physically induced mutagenesis [2]. It was also reported that vanillin exhibits antimicrobial properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…Natural vanilla extract from reported that vanillin is able to suppress the proliferation of cancer cells and prevent chemically and physically induced mutagenesis [2]. It was also reported that vanillin exhibits antimicrobial properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mourtzinos, Konteles, Kalogeropoulos y Karathanos (2009) reportaron que las bacterias Gram-negativas son ma´s sensibles que las Gram-positivas ante la presencia de vainillina, y que la concentracio´n mı´nima inhibitoria para S. aureus es de 1200 mg/kg. Tambie´n se han publicado una gran cantidad de estudios acerca del efecto de la vainillina como sustancia antimicrobiana en diferentes tipos de microorganismos (Cerrutti & Alzamora, 1997;Delaquis, Stanich, & Toivonen, 2005;Lo´pez-Malo et al, 2005;Rupasinghe, Boulter-Bitzer, Ahn, & Odumeru, 2006;Ngarmsak et al, 2006), en los cuales el factor comu´n es el requerimiento de altas concentraciones de vainillina para inhibir el crecimiento microbiano (entre 1000 y 1500 mg/kg para inhibicio´n in vitro). En nuestro caso, la combinacio´n de temperatura, a w y pH favorece la utilizacio´n de menores concentraciones de vainillina para inactivar a S. aureus.…”
Section: Modelizacio´n Secundariaunclassified
“…IR spectra were recorded on FTIR 3700 spectrophotometer Schimadzu in the range 4000-400 cm -1 . Proton NMR and 13 CNMR were recorded on Varian MR-400MHz in CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…A peak is designated at δ 3.09 for methoxy methyl protons. 13 CNMR ( Table 2) spectrum exhibits a characteristic downfield singlet at δ 190.29 for aldehydic carbonyl carbon. A singlet is appeared at δ 161.40 for C-4 carbon atom possessing hydroxy group.…”
Section: Fig 1 Structure Of Vanillinmentioning
confidence: 99%
See 1 more Smart Citation